Effect of stanum doping and heat treatment on Bi-Sr-Ca-Cu-O superconducting ceramics - Hashim @ Ismail, Azhan (1999)
The influence of Sn doping in calcium (Ca) and copper (Cu) sItes either temperature for 30 hours soaking time were studied For Sn-free sample. heat treatment improved the superconducting transition temperature, TC(RI)) from 100 K to 104 K, when the sintered sample was annealed at 820°C The highest Tc(R=0) of 104 K was observed for sintered sample (x=0 02) with simultaneous doping The heat treatment improved the Tc(R=0) from 60 K to 94 K or sample doped 111 Ca site when re-sintered at 855°C and from 66 K to 100 K for sample doped with Sn in Cu site when annealed at 840°C For simultaneous doping, the T C(R 0) dId not change significantly after heat treatment except for sample with x=0 05 that showed drastic improvement of T C(R=U) from 64 K (sintered) to above 100 K From XRD analysis, the volume of 2223 phase decreased as the Sn concentration increased A ll samples with Sn concentration above x=0 10 contall1ed unknown peaks which con respond to the non-superconducting phase although the lattice parameter of the samples shortened, the crystallographic structure remained in the tetragonal form.